2013
DOI: 10.1042/bj20121622
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function analysis of full-length midkine reveals novel residues important for heparin binding and zebrafish embryogenesis

Abstract: Midkine is a heparin-binding di-domain growth factor, implicated in many biological processes as diverse as angiogenesis, neurogenesis and tumorigenesis. Elevated midkine levels reflect poor prognosis for many carcinomas, yet the molecular and cellular mechanisms orchestrating its activity remain unclear. At the present time, the individual structures of isolated half domains of human midkine are known and its functionally active C-terminal half domain remains a popular therapeutic target. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…Lim and coworkers have studied the structural binding mechanism of fondaparinux and a natural heparin to midkine, a heparin-binding di-domain growth factor [52]. Results have indicated that residues W55, K56 and K57 in the hinge, which are spatially located between basic clusters 1 and 3 of both composing domains, are involved in the heparin binding.…”
Section: System Development: Morphogensmentioning
confidence: 95%
“…Lim and coworkers have studied the structural binding mechanism of fondaparinux and a natural heparin to midkine, a heparin-binding di-domain growth factor [52]. Results have indicated that residues W55, K56 and K57 in the hinge, which are spatially located between basic clusters 1 and 3 of both composing domains, are involved in the heparin binding.…”
Section: System Development: Morphogensmentioning
confidence: 95%
“…The interaction between the multifunctional growth factor midkine and heparin is unusual in that the hinge region between the two domains is important for heparin binding, as determined by an NMR study using the pentasaccharide fondaparinux (Lim et al, 2013). Pleiotrophin is associated with chondroitin sulfate-mediated neurite outgrowth and is important in bone repair (Lamprou et al, 2014).…”
Section: Heparin and Cytokines Growth Factors Selectins And Promentioning
confidence: 99%
“…In particular, there is a flexible loop in the middle of the C‐domain (amino acids 86–93), and a pocket is created in the domain (Figure ). Recently, detailed analysis of the whole molecule of zebrafish Mdkb has been performed and has revealed the whole structure of MK, including the hinge region, which has an extended structure (Lim et al ., ).…”
Section: Mk Proteinmentioning
confidence: 97%
“…N‐domain has functions different from those of C‐domain. Firstly, another heparin‐binding site has been identified in the N‐domain of Mdkb (Lim et al ., ). The key residue of the new binding site is R36, corresponding to R35 in human MK (Lim et al ., ).…”
Section: Mk Proteinmentioning
confidence: 97%
See 1 more Smart Citation